Modeling Cardiomyopathies in a Dish: State-of-the-Art and Novel Perspectives on hiPSC-Derived Cardiomyocytes Maturation - Lodola, Francesco (2021)
The stem cell technology and the induced pluripotent stem cells (iPSCs) production represent an excellent alternative tool to study cardiomyopathies, which overcome the limitations associated with primary cardiomyocytes (CMs) access and manipulation. CMs from human iPSCs (hiPSC–CMs) are genetically identical to patient primary cells of origin, with the main electrophysiological and mechanical features of CMs. The key issue to be solved is to achieve a degree of structural and functional maturity typical of adult CMs. In this perspective, we will focus on the main differences between fetal-like hiPSC-CMs and adult CMs. A viewpoint is given on the different approaches used to improve hiPSC-CMs maturity, spanning from long-term culture to complex engineered heart tissue. Further, we outline limitations and future developments needed in cardiomyopathy disease modeling.